Effects of Tax Morale on Tax Compliance: Experimental and Survey Evidence - Ronald G. Cummings; Jorge Martinez-Vazquez; Michael McKee; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2005)
There is considerable evidence that enforcement efforts can increase tax compliance. However, there must be other forces at work because observed compliance levels cannot be fully explained by the level of enforcement actions typical of most tax authorities. Further, there are observed differences, not related to enforcement effort, in the levels of compliance across countries and cultures. To fully understand differences in compliance behavior across cultures one needs to understand differences in tax administration and citizen attitudes toward governments. The working hypothesis is that cross-cultural differences in behavior have foundations in these institutions. Tax compliance is a complex behavioral issue and its investigation requires the use of a variety of methods and data sources. Results from laboratory experiments conducted in different countries demonstrate that observed differences in tax compliance levels can be explained by differences in the fairness of tax administration, in the perceived fiscal exchange, and in the overall attitude towards the respective governments. These experimental results are shown to be robust by replicating them for the same countries using survey response measures of tax compliance.
Keywords: H20; C90; 330